2019
DOI: 10.1038/s41598-018-37313-z
|View full text |Cite
|
Sign up to set email alerts
|

SLIME: robust, high-speed 3D microvascular mapping

Abstract: Three dimensional (3D) microvascular imaging of cubic millimeter to centimeter size volumes often requires much time and expensive instruments. By combining optical clearing with a novel scatter-based optical coherence tomography (OCT) contrast agent, we have greatly extended OCT imaging depth in excised tissues while maintaining a simple and low cost approach that does not require in-depth OCT knowledge. The new method enables fast 3D microvascular mapping in large tissue volumes, providing a promising tool f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The spatial organization of the developing coronaries had not been quantified, with previous studies conducted in turkeys, chickens, mice and humans focusing on capillary density 8,[10][11][12][13]44,45 . Our recent study in quails 23 uncovered highly aligned coronary microvessels at the newly septate embryonic heart surface instead of a plexus of coronaries as in preceding stages 49,50 . This strong alignment disappeared when the embryos were dosed with ethanol in a model of prenatal alcohol exposure, but the vessel alignment in neither the healthy nor the diseased hearts were quantified.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The spatial organization of the developing coronaries had not been quantified, with previous studies conducted in turkeys, chickens, mice and humans focusing on capillary density 8,[10][11][12][13]44,45 . Our recent study in quails 23 uncovered highly aligned coronary microvessels at the newly septate embryonic heart surface instead of a plexus of coronaries as in preceding stages 49,50 . This strong alignment disappeared when the embryos were dosed with ethanol in a model of prenatal alcohol exposure, but the vessel alignment in neither the healthy nor the diseased hearts were quantified.…”
Section: Discussionmentioning
confidence: 80%
“…Cardiomyocyte disarray has been observed in the mouse embryo as a precursor to hypertrophic cardiomyopathy 32 and could contribute to a disorganized vasculature by affecting the maturation of the vascular plexus. In a previous study, we observed abnormal coronary microvascular alignment in the ventricular wall in a model of fetal alcohol spectrum disorders 23 . These abnormalities included chaotic microvasculature patterns and regions of missing vasculature.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations